ANALISIS SEMIOTIK SYAIR KESENIAN SOLAWAT DULANG TUBUAH NAN SALAPAN SINAR BARAPI DAN DC 8 - Ahmad Syafari (Mozaic : Islam Nusantara, 2020)
The art is one of many metodes that very used by muslim people to share the Islamic Knowledges or for doing dakwah. With the art, the points of Islamic Knowledge will be more interest and usefull, that because Knowledge of Islamic is will packed to be more fun and to the most something nice. But now in modern era, the art of Islamic is not interesting for modern people, especially the Islamic traditional art is already erased by the time because many people just like tolook the performing don’t to know what the message from that art. One of somany the islamis traditional art that must to understand what a message inside it is a traditional art Solawat Dulang from Minangkabau , West Sumatra. This research try to find the meaning from every single from the song that be object from this and to get the Islamic message that inside the song. To get the goal, this research use the research metode kualitative and descriptive with technic analysis semiotic Roland Barthes to find the meaning from the song and Islamic messeage theory to get the Islamic knowledge from all the song. Technic Collecting Data from this research is Documentary. In generally, Solawat Dulang Tubuah Nan Salapan by Sinar Barapi and DC 8 tell about relation between body jasmani or fisicly is body that look by eye and body rohani is thebody that stay in body jasmani. The Islamic message from the Solawat Dulang are Aqidah message, there is the tauhid message, believe to the propet Muhammad and the death day. The law or syariah message are studying and try to understand theQuran. And the akhlak message are about the bad act, the etica in niaga, and the etica be the teacher to give the islamic knowledge must to be honest.